Spawning biology of snow trout, Schizothorax richardsonii (Gray) from River Gaula (Kumaon, Himalaya) - Mohan, Madan (Indian Journal of Fisheries, 2011)
Studies on the reproductive biology of snow trout, Schizothorax richardsonii from River Gaula revealed that the species spawns twice in a year (July-October and January-February) as evidenced from the occurrence of ripe fishes, high GSI values during the above period and from bimodal ova diameter polygon. The male to female ratio was 1: 1.09. The fecundity ranged from 2248 to 8726 in fishes of 160- 245 mm TL and 40-110gm weight. The relation between fecundity and fish length, fish weight and ovary weight were also attempted